Potential of bio-hydrogen production by C. pasteurianum co-immobilized with selected nano-metal particles. (19th March 2021) - Wannapokin, Anongnart; Cheng, Yu-Tzu; Wu, Sheng-Zhe; Hsieh, Ping-Heng; Hung, Chun-Hsiung
Abstract: Currently, green energy has gained considerable interest as an economical source of energy. Compared with other alternative energy sources, hydrogen has a considerable environment-friendly potential. Microorganisms that possess hydrogen production ability have been investigated. Direct mixing of nano-metals with microorganisms under suspended growth has been proven to increase hydrogen production. In this study, a novel approach of co-immobilization of nano-metals and hydrogen-producing microorganism was proposed. Accumulative gas production and composition showed that co-immobilization with nano-metal nickel (NP–Ni) and iron (NP–Fe) improved system performance. Adding 400 ml/L of NP-Ni and 200 ml/L of NP-Fe enhanced composition percentage of hydrogen gas to 46.90% and 42.03%, respectively. Co-immobilized granules could endure up to 14 days of operation, and some cracked into two halves at 22 days. However, hydrogen production remained consistent throughout the experiment. Thus, results demonstrated that Clostridium pasteurianum co-immobilized with selected nanometal particles could be a feasible method to increase hydrogen production. Graphical abstract: Image 1 Highlights: Change three bullet points to the followingCo-immobilization of hydrogen-producing microorganism and nano-metal is proposed. Immobilization obtained better hydrogen producing performance than suspended growth. The immobilized cells could withstand two weeks of operation without breaking up.